2020
DOI: 10.1093/eurpub/ckaa184
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a questionnaire to assess Unaccompanied Migrant Minors’ needs (AEGIS-Q)

Abstract: Background While many studies focus on specific aspects of Unaccompanied Migrant Minors’ (UMMs) health, especially mental well-being, there is a lack of tools comprehensively assessing their needs. To fill this gap, we developed and validated a questionnaire to thoroughly assess unAccompaniEd miGrant mInorS’ physical, psychological, legal, spiritual, social and educational needs (AEGIS-Q). Methods This work consisted of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Eleven studies were identified that investigated mental health screening approaches specific to refugee children and adolescents [ 52 , 57 , 58 , 59 , 61 , 62 , 67 , 82 , 89 , 97 , 100 ]. Children and adolescents between the ages of 6 months to 18 years old were included and all identified screening programs were completed post-arrival to the resettlement country.…”
Section: Mental Health Screening Approaches For Refugee Children and ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies were identified that investigated mental health screening approaches specific to refugee children and adolescents [ 52 , 57 , 58 , 59 , 61 , 62 , 67 , 82 , 89 , 97 , 100 ]. Children and adolescents between the ages of 6 months to 18 years old were included and all identified screening programs were completed post-arrival to the resettlement country.…”
Section: Mental Health Screening Approaches For Refugee Children and ...mentioning
confidence: 99%
“…A total of 25 studies evaluated the validity of mental health screening tools among a cumulative sample of N = 4341 refugees and asylum seekers [ 42 , 44 , 46 , 48 , 50 , 52 , 55 , 64 , 65 , 66 , 67 , 70 , 72 , 80 , 82 , 86 , 87 , 89 , 95 , 99 , 100 , 101 , 105 , 106 ]. All of the included studies followed a cross-sectional study design.…”
Section: Mental Health Screening Tool Validation Studiesmentioning
confidence: 99%
See 1 more Smart Citation